Fabrication, characterization, and testing of activated carbon-nickel (II) oxide electrodes for capacitive deionization of aqueous sodium chloride solution - Gandionco, Karl Adrian; Ocon, Joey D. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
Water scarcity has been a global problem for the past several decades. About 71% of the Earth's surface is covered by water, but still two-thirds of the world's population currently live in areas that experience water scarcity for at least one month a year. Water scarcity is becoming more severe by the year as the demand for clean water has been increasing brought by the unhindered growth of global population. Moreover, their responsible exploitation of water resources has resulted in a shortage of fresh water supply. Currently, only 0.5% of the 1.4 billion cubic kilometers of water in the world is accessible fresh water. The state of the world's fresh water supply and the vastness of the sea water have paved the way to the development of desalination technologies as alternative sources of clean water. In this work, activated carbon-nickel (II) oxide (ACNiO) electrodes were studied as materials for the capacitive deionization (CDI) of aqueous sodium chloride solution. The AC-NiO electrodes were fabricated by mixing activated carbon, nickel (II) oxide, polyvinylidene fluoride binder, and N-methyl-2 pyrrolidone solvent on a magnetic hotplate stirrer at 60°C for a total of 3 hours. The amount of nickel (II) oxide was varied and its effect on the deionization performance was investigated. Scanning electron microscopy reveals that the pure carbon and the AC-NiO electrodes have similar morphology. However, results of the energy dispersive X-ray, X-ray diffraction, and the Thermogravimetric analysis show that nickel (II) oxide was successfully and proportionally mixed with the carbon material. Cyclic voltammograms of the as-prepared electrodes reveal that the deionization of the solution was mainly due to the electrochemical double layer formation and there was no significant contribution from Faradaic reactions. Moreover, electrochemical impedance spectroscopy shows that the AC-NiO electrodes have slightly higher diffusion resistance compared to the pure carbon electrode. Among all the as-prepared electrodes, the AC Nio electrode with approximately 10 percent of nickel (II) oxide (AN-10) gives the highest salt adsorption capacity and charge efficiency which are equal to 7.5 mg/g and 90.1% respectively. This finding can be attributed to the optimum enhancement of the physical and chemical characteristics of the electrode material. Furthermore, the deionization performance of the AN-10 electrode is comparable to that of carbon-metal oxide CDI electrodes in the literature. To the best of the author's knowledge, this is the first study in CDI literature that shows the feasibility of AC-NiO as electrodes for the deionization of aqueous sodium chloride solution.
Thesis (Master of Science in Chemical Engineering)--University of the Philippines Diliman
Keywords: Saline water conversion; Capacitive deionization (CDI).